Suppression of a Field Population of Aedes aegypti in Brazil by Sustained Release of Transgenic Male Mosquitoes. - Danilo O Carvalho; Andrew R McKemey; Luiza Garziera; Renaud Lacroix; Christl A Donnelly; Luke Alphey; Aldo Malavasi; Margareth L Capurro (PLoS Neglected Tropical Diseases)
The increasing burden of dengue, and the relative failure of traditional vector control programs highlight the need to develop new control methods. SIT using self-limiting genetic technology is one such promising method. A self-limiting strain of Aedes aegypti, OX513A, has already reached the stage of field evaluation. Sustained releases of OX513A Ae. aegypti males led to 80% suppression of a target wild Ae. aegypti population in the Cayman Islands in 2010. Here we describe sustained series of field releases of OX513A Ae. aegypti males in a suburb of Juazeiro, Bahia, Brazil. This study spanned over a year and reduced the local Ae. aegypti population by 95% (95% CI: 92.2%-97.5%) based on adult trap data and 81% (95% CI: 74.9-85.2%) based on ovitrap indices compared to the adjacent no-release control area. The mating competitiveness of the released males (0.031; 95% CI: 0.025-0.036) was similar to that estimated in the Cayman trials (0.059; 95% CI: 0.011-0.210), indicating that environmental and target-strain differences had little impact on the mating success of the OX513A males. We conclude that sustained release of OX513A males may be an effective and widely useful method for suppression of the key dengue vector Ae. aegypti. The observed level of suppression would likely be sufficient to prevent dengue epidemics in the locality tested and other areas with similar or lower transmission.